Strengthening the Meteorological Sounding Network Over the Eastern Pacific Ocean and the Intertropical Americas to support pacs - Douglas, Michael W. (1997)
The present atmospheric sounding network over Central America and Northern South America does not reliably depict the structure of the Intertropical Convergence Zone (ITCZ) over the region. Over the eastern tropical Pacific no soundings are routinely made, except for recently renewed soundings in the Galapagos Islands. Thus, the variability of the ITCZ on all time scales, from daily to seasonal and interannual, can only be described over much of the PACS domain from a satellite perspective. The lack of detailed sounding information prevents many questions from being answered in a confident manner. Such questions include: (1) Do major systematic errors exist in the routine NMC and ECMWF analyses over the eastern tropical Pacific? How closely does the actual mean structure of the ITCZ in the far eastern Pacific resemble that routinely analyzed by operational centers? 2. Does the current radiosonde network in central America provide an accurate depiction of the lower-tropospheric flow in this region? (3) What large-scale meteorological conditions are associated with dry and wet spells over Central America during the May-October rainy season? The primary objective of this proposal is to establish an enhanced atmospheric sounding network over the eastern tropical Pacific Ocean and bordering regions for a period of up to 18 months. At the end of this period we believe that enough data (both meteorological and operational experience) will have been collected to determine the desirability and feasibility of sustaining the network operation for the duration of PACS. The observations will include radiosonde and pilot balloon soundings, to be made in 4 countries. These data will be available to support many PACS investigators. During the first year of operation we will establish the feasibility of operating the stations for an indefinite period and determine which network configuration is most cost-effective for addressing PACS objectives. We intend to address the three questions posed above once data from one boreal warm season has been obtained by the network.